Improvement Of Pancasila Education Learning Outcomes Through The Culturraly Responsive Teaching Approach Assisted By Media Recalling Cards In Grade Iv Elementary School - Hendra Permatasari, Dessy Ariska; Mursidik, Elly's Mersina; Sujianti, Reni (Jurnal Impresi Indonesia, 2024)
The low results Study students caused by lack of relevance approach learning with background behind culture students. Combination CRT approach with Recalling Card media is designed For give experience learning that is relevant, interactive, and meaningful for students. Research This aiming For increase results Study student class IV Sobrah State Elementary School on the eyes Pancasila Education lessons through approach Teaching Responsive Culture (Culturally Responsive Teaching/CRT) assisted by Recalling Card media. Study This use method Classroom Action Research (CAR) with approach descriptive qualitative. Subject study is 23 students fourth grade at Sobrah State Elementary School. Data is collected through observation, testing, documentation, and interviews. Research implemented in two cycles, each consisting of from stage planning, action, observation, and reflection. Data analysis techniques used is descriptive qualitative with steps data reduction , data presentation, and conclusion and verification . Research results show existence significant improvement in results? Study students. In the cycle first. percentage completeness reached 69.6%, while in the cycle second increase to 86.9%. The CRT approach allows student For understand material through context culture them. while the Recalling Card media helps increase concentration and participation student. Implications study This is approach Teaching Responsive Culture assisted by Recalling Card media can used as a learning strategy innovative that supports implementation Independent Curriculum. Teachers are advised For integrate aspect culture local in learning For increase relevance and meaningfulness material for students. Research This give contribution important in development method responsive learning? to diversity culture in Indonesia.